THE IMPORTANCE OF TECHNOLOGY INTEGRATION IN BIOLOGY LEARNING IN THE DIGITAL ERA - Cartono Cartono (INFOKUM, 2022)
In the context of the rapid development of information and communication technology, conventional approaches in biology learning need to be reconsidered in order to utilize the potential of existing technology. This research aims to investigate and analyze the importance of technology integration in biology learning in the digital era. This research uses a qualitative approach with descriptive methods. The research results show that the integration of technology in biology learning increases engagement and learning effectiveness. The use of simulation software, interactive videos, and learning applications motivates students and provides an immersive learning experience. Personalization of learning through digital platforms and adaptive learning improves student understanding. Online learning data provides targeted feedback, while collaborative projects and virtual interactions build collaboration skills. Overall, technology integration creates an adaptive, interactive, and relevant learning environment in the digital era.